Sustainable energy consumption in African higher institutions of learning: the nexus of top management commitment and institutional pressures - Arinaitwe, Alice; Aikiriza, Fiona Apofia; Kakooza, John Bosco; Bagire, Vincent (Emerald, 2024)
Purpose This study investigates the nexus of top management commitment and institutional pressures towards enhancing sustainable energy consumption in African Higher Institutions of Learning. Design/methodology/approach Using a structured questionnaire survey, cross-sectional data collected from 64 higher institutions of learning registered with the Uganda National Council for Higher Education were analyzed using the Statistical Package for Social Sciences (SPSS). Findings The findings revealed that top management commitment and institutional pressures individually associate with sustainable energy consumption. Top management commitment does not cause variations in sustainable energy consumption. However, when top management commitment coalesces with institutional pressures, they significantly predict sustainable energy consumption. Research limitations/implications The current study focuses on Higher Institutions of Learning in Uganda. Hence caution should be taken before generalization of findings. This study therefore sets ground for future studies to investigate sustainable energy consumption in other institutions. Originality/value This study tests the efficacy of top management commitment and institutional pressures on sustainable energy consumption using evidence from African Higher Institutions of Learning. It provides new directions for study in such a nascent area of critical national dimension as sustainability and climate change issues top the global agenda.